Gene-based therapies in patients with critical limb ischemia. (3rd April 2017) - Kitrou, Panagiotis; Karnabatidis, Dimitris; Brountzos, Elias; Katsanos, Konstantinos; Reppas, Lazaros; Spiliopoulos, Stavros
ABSTRACT: Introduction : Critical limb ischemia (CLI) constitutes a life-limiting and life-threatening disease. Revascularization, either endovascular or surgical, remains the best treatment option accompanied by medication and risk factor modification. Patients unable to undergo revascularization, referred as 'no-option patients', have been the center of interest the last few years, subjected to treatment therapies based on proteins (mainly growth factors) involved in angiogenesis via gene delivery to the ischemic tissue. Areas covered : This review focuses on these growth factors, gives an update of the studies available, discusses the possible problems that influence outcomes and describes future perspectives including possible new technologies that will improve them. Additionally, the authors attempt to place therapeutic angiogenesis to the bigger frame of tailored therapy in CLI. Expert opinion : Although encouraging in the beginning, growth factor therapy results have been equivocal and inconclusive. And while it would be misleading to approach gene therapy as panacea, its effect on the micro-circulatory level activating angiogenesis and arteriogenesis could act as an important adjunct in personalized treatment.